Genomic Diversity and Species Boundaries of the Chilean Silversides Fishes (Atheriniformes, Atherinopsidae) - Briñoccoli, Yanina Florencia (2025)
Silverside fishes in Chile, abundant in marine and freshwater habitats, are classi- fied in two genera: Odontesthes and Basilichthys. Both genera have widespread distributions across southern South America, with marine origins. Despite extensive information on Chilean freshwater silversides and their overlapping distributions along a latitudinal gradient, their taxonomy and diversification remain contentious. This study examines the diversity of Chilean silversides using RADseq genomic data from 78 Odontesthes and 60 Basilichthys individuals, covering most of their range. The phylogenetic and structural analyses of approximately 20,000 SNPs reveal some geographic variation but indicate no differentiation between Odontesthes mauleanum and O. brevianalis. The genus Basilichthys, in contrast, presents a disjunct distribution, with populations in coastal rivers of Peru (B. semotilus) that are separated from Chilean populations by the Atacama Desert. Chilean Basilichthys, traditionally classified as B. microlepidotus and B. australis until 2012, also show no genetic differentiation consistent with species boundaries but exhibit latitudinal differences consistent with isolation by distance. The contrasting patterns of genetic dif- ferentiation exhibited by species of these genera may be explained by the more frequent exchange with marine species for Odontesthes that do not occur in Basilichthys, in addition to the recent geological history of glaciations affecting the southern range of their distribution.